Rancang Bangun Sistem Aplikasi Bank Sampah Online Berbasis Android Di Bank Sampah Lintas Winongo - Rajasa, Bagas Rangga; Sejati, RR. Hajar Puji (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Lintas Winongo Waste Bank in Kampung Badran, Jetis, Yogyakarta, has been serving as a community facilitator in addressing waste issues in Kampung Badran since 2009. Despite having numerous customers, the waste bank management is still conducted manually, leading to various service issues such as bookkeeping transactions and waste management that rely on manual processes. The sustainability of using a manual system also poses the potential for data damage and the risk of errors in the data input stage, negatively impacting the overall efficiency and accuracy of waste management. Therefore, an application system for the waste bank is needed to facilitate transactions for both customers and waste bank operators in waste management. This research employs the waterfall method with a focus on the needs of Lintas Winongo Waste Bank. The system testing involves the black box testing method. The results of this study provide convenience for both customers and waste bank operators in every transaction process. The use of this system is expected to simplify and expedite the waste deposit process conducted by customers, aiming to increase community interest in utilizing waste bank services.